Diseño de máquina portátil para corte de banda de rodadura de llantas usadas (2023)
The production of used tires is a serious environmental problem worldwide, since billions of tires are produced every year, which eventually become unusable and have to be discarded, causing serious damage to the environment and public health by being disposed of improperly. This project aims to design a tire cutting machine, which is part of the Tire Waste Recovery project with a circular economy approach-SENA-FUA, in addition to improving the environmental conditions of the city and the country through the treatment proper disposal of scrap tires. The machine design process began thanks to bibliographic research on tread cutting machines designed to obtain the necessary application parameters. Laboratories were carried out with a cutting device created for a universal testing machine.